Digital Waqf as a Social Impact Model: A Framework for Sustainable Funding of Islamic Education via Technology Platforms - Ali Iskandar Zulkarnain; Ahmed Al-Mohannadi; Salim Al-Zayani (Islamic Studies in the World, 2025)
The growing demand for sustainable and reliable funding models in Islamic education has intensified interest in the digitalization of waqf as a contemporary social impact mechanism. Traditional waqf systems, while historically significant in supporting schools, madrasahs, and Islamic higher education, often struggle with management inefficiencies, limited transparency, and low donor engagement. Digital waqf platforms supported by FinTech and blockchain technologies offer new opportunities to revive waqf as a scalable and accountable funding model capable of sustaining educational institutions in the modern era. This study aims to develop a conceptual framework that explains how digital waqf can function as a sustainable social impact model to finance Islamic educational institutions. The research evaluates the technological, managerial, and ethical components that enable digital waqf to improve fundraising, enhance governance, and promote long-term financial resilience. It also investigates donor perceptions and platform characteristics that influence participation in digital waqf systems. A qualitative research design was employed using systematic literature review, analysis of digital waqf platforms, and semi-structured interviews with waqf administrators, Islamic education leaders, and technology developers. The data were analyzed thematically to identify operational features, governance structures, and technology-driven innovations that shape the effectiveness of digital waqf ecosystems. The findings indicate that digital waqf platforms significantly improve transparency, reduce administrative barriers, and expand donor outreach through automated reporting, smart contracts, and mobile-based contribution tools. These innovations enhance donor trust and strengthen institutional accountability. The study concludes that digital waqf has substantial potential to become a sustainable funding model for Islamic education when supported by strong governance, ethical compliance, and user-centered technological design.